2021
DOI: 10.20944/preprints202104.0091.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tired, Worried and Burned Out But Still Resilient: A Cross-Sectional Study of Mental Health Workers During the Covid-19 Pandemic

Abstract: The burden of COVID-19 pandemic on health systems and the physical and mental health of healthcare workers (HCWs) has been substantial. This cross-sectional study aims to assess the effects of Covid-19 on the psychological wellbeing of mental health workers who provide care to a vulnerable patient population that have been particularly affected during this crisis. A total of 387 HCWs from across a large urban mental health service completed a self-administered questionnaire consisting of socio-demographic, lif… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 55 publications
1
6
0
2
Order By: Relevance
“…Several previous studies demonstrated a higher psychological impact for frontline staff, yet others showed that the mental health effects of the crisis were equally felt across settings or specialties. [60][61][62] Overall, anxiety symptoms were more frequent than depression, a common finding across most studies to date. 55 Despite the considerable between-study heterogeneity, it appears that comparable proportions of respondents across groups recorded mild and moderate symptoms both for depression and anxiety, while more severe symptoms were less common.…”
Section: Comparison Of Results With Previous Studiesmentioning
confidence: 91%
See 1 more Smart Citation
“…Several previous studies demonstrated a higher psychological impact for frontline staff, yet others showed that the mental health effects of the crisis were equally felt across settings or specialties. [60][61][62] Overall, anxiety symptoms were more frequent than depression, a common finding across most studies to date. 55 Despite the considerable between-study heterogeneity, it appears that comparable proportions of respondents across groups recorded mild and moderate symptoms both for depression and anxiety, while more severe symptoms were less common.…”
Section: Comparison Of Results With Previous Studiesmentioning
confidence: 91%
“…Furthermore, in our review, general and frontline staff recorded similar levels of psychological distress. Several previous studies demonstrated a higher psychological impact for frontline staff, yet others showed that the mental health effects of the crisis were equally felt across settings or specialties 60–62 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in our review, general and frontline staff recorded similar levels of psychological distress. Several previous studies demonstrated a higher psychological impact for frontline staff, yet others showed that the mental health effects of the crisis were equally felt across settings or specialties [58][59][60].…”
Section: Comparison Of Results With Previous Studiesmentioning
confidence: 97%
“…More than half of mental healthcare workers (52%) experienced sleep problems during pandemics in the UK. 44 A study of 939 healthcare workers in Turkey during the first wave of the pandemic, 50% of participants reported sleep problems. 13 Poor sleep quality (PSQI ≥ 5) was identified at a rate of 75.2% in a study of 257 healthcare workers in Bahrain.…”
Section: Discussionmentioning
confidence: 99%